Reducing the search space and time complexity of Needleman-Wunsch Algorithm (Global Alignment) and Smith-Waterman Algorithm (Local Algorithm) for DNA sequence alignment - Fatimah Noni Muhamad (School of Computer and Communication Engineering, 2011)
The main research in this project is to align the DNA sequences by using the Needleman-Wunsch algorithm for global alignment and Smith-Waterman algorithm for local alignment based on the Dynamic Programming algorithm.